2006
DOI: 10.1016/j.febslet.2006.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of TPPP/p25 protein with glyceraldehyde‐3‐phosphate dehydrogenase and their co‐localization in Lewy bodies

Abstract: TPPP/p25, a flexible unstructured protein, binds to tubulin and induces aberrant microtubule assemblies. We identified hereby glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as a new interacting partner of TPPP/p25. The immunoprecipitation and affinity chromatographic experiments with bovine brain cell-free extract revealed that the interaction was salt and NAD + sensitive while ELISA showed resistant and firm association of the two isolated proteins. In transfected HeLa cells at low expression level of EGFP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…the oligodendroglial cytoplasm and all oligodendroglial processes [7,8], two studies previously reported that TPPP is localized in the nucleus [10,20], consistent with the present data. Höftberger and colleagues previously analyzed the localization of TPPP in the human brain by immunohistochemistry and immunoelectron microscopy, and showed that TPPP was localized in oligodendroglial nuclei as well as its cytoplasm [10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…the oligodendroglial cytoplasm and all oligodendroglial processes [7,8], two studies previously reported that TPPP is localized in the nucleus [10,20], consistent with the present data. Höftberger and colleagues previously analyzed the localization of TPPP in the human brain by immunohistochemistry and immunoelectron microscopy, and showed that TPPP was localized in oligodendroglial nuclei as well as its cytoplasm [10].…”
Section: Discussionsupporting
confidence: 81%
“…TPPP is also essential for the reorganization and stabilization of microtubules [2,5]. Another characteristic biochemical feature of TPPP is that it normally remains as an unfolded and unstructured protein without binding partners [6], whereas in the presence of proteins such as myelin basic protein (MBP) or tubulin [2,[7][8][9], it changes its secondary structure and exerts physiological roles such as binding with tubulin to stabilize microtubules [2,5]. TPPP is also a guanosine triphosphate (GTP)-binding protein, which hydrolyzes GTP to produce guanosine diphosphate (GDP), and participates in multiple physiological functions [9].…”
Section: Introductionmentioning
confidence: 99%
“…4A shows the proteins that were bound to the affinity column, and then eluted by 0.5 M NaCl. The two dominant bands in the gel correspond to tubulin and GAPDH as reported earlier (6). Between these two bands the marked band was excised and in-gel digested with trypsin.…”
Section: Resultsmentioning
confidence: 99%
“…Affinity Chromatography-Human recombinant TPPP was immobilized to CNBr-activated Sepharose 4B (Amersham Biosciences) and used for finding interacting proteins from bovine brain extract as described previously (6). The bound proteins were eluted with 10 mM phosphate buffer, pH 7.0, containing 0.5 M NaCl, and the protein bands obtained by SDS-PAGE (19) were analyzed by mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…GAPDH and Hsp90 only interacted with the FKBP36 affinity matrix, whereas no binding was observed to the matrix alone. The FKBP36 TPR Domain Binds GAPDH and Hsp90-To test whether FKBP36 binds directly to GAPDH, we made use of purified GAPDH from rabbit muscle, which was previously utilized in several similar studies (11)(12)(13). Isolated GAPDH was incubated with the GST-FKBP36 affinity matrix.…”
Section: Fkbp36mentioning
confidence: 99%